Histological and Finite Element Analysis of Cell Death Due to Irreversible Electroporation. (December 2014) - Long, G.; Bakos, G.; Shires, P. K.; Gritter, L.; Crissman, J. W.; Harris, J. L.; Clymer, J. W.
Irreversible electroporation (IRE) has been shown to be an effective method of killing cells locally. In contrast to radiofrequency ablation, the mechanism by which cells are thought to die via IRE is the creation of pores in cell membranes, without substantial increase in tissue temperature. To determine the degree to which cell death is non-thermal, we evaluated IRE in porcine hepatocytes in vivo . Using pulse widths of 10μs, bursts of 3 kV square-wave pulses were applied through a custom probe to the liver of an anesthetized pig. Affected tissue was evaluated histologically via stainings of hematoxylin & eosin (H&E), nitroblue tetrazolium (NBT) to monitor cell respiration and TUNEL to gauge apoptosis. Temperature was measured during the application of electroporation, and heat transfer was modeled via finite element analysis. Cell death was calculated via Arrhenius kinetics. Four distinct zones were observed within the ring return electrode; heat-fixed tissue, coagulation, necrotic, and viable. The Arrhenius damage integral estimated complete cell death only in the first zone, where the temperature exceeded 70°C, and partial or no cell death in the other zones, where maximum temperature was approximately 45°C. Except for a limited area near the electrode tip, cell death in IRE is predominantly due to a non-thermal mechanism.